Infecção por fusarium graminearum e fusarium verticillioides em sementes de milho - Ramos, Dayana Portes [UNESP]; Barbosa, Rafael Marani [UNESP]; Vieira, Bruno Guilherme Torres Licursi [UNESP]; de Cássia Panizzi, Rita [UNESP]; Vieira, Roberval Daiton [UNESP] (My University, 2014)
The previous knowledge of the infection process and pathogens behavior, for evaluating the physiological potential of maize seeds, is essential for decision making on the final destination of lots that can endanger sowing. This research was carried out in order to study the minimum period required for maize seeds contamination by Fusarium graminearum Schwabe and Fusarium verticillioides (Sacc.) Nirenberg, as well as these pathogens influence on seed germination and vigor, by using the cold test. Three maize seeds hybrids, kept in contact with the pathogens for different periods, were evaluated with and without surface disinfection. After determining the most suitable period, new samples were contaminated by F. graminearum and F. verticillioides, under different infection levels, and subjected to germination tests in sand. The cold test was conducted with healthy and contaminated seeds, at different periods, in a cold chamber. The contact of maize seeds with F. graminearum and F. verticillioides for 16 hours was enough to cause infection. F. graminearum and F. verticillioides did not affect the maize seeds germination, however, F. graminearum reduced the vigor of seeds lots.
Fusarium graminearum and fusarium verticillioides infection on maize seeds
Keywords: Cold test; Seed pathology; Zea mays L.